2020
DOI: 10.3390/ijerph17124402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leisure Participation on Life Satisfaction in Older Korean Adults: A Panel Analysis

Abstract: South Koreans’ life expectancy has dramatically increased over the last four decades. However, the life satisfaction index of older Korean adults has been in the bottom third globally. The large majority of older Koreans spend most of the day watching television at home. However, concrete evidence regarding the effects of leisure involvement on older adults’ quality of later life is scant. Only a few existing studies have examined the link via cross-sectional survey data. Thus, the purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
2
33
0
2
Order By: Relevance
“…Leisure activity participation is regarded as a factor that may influence the health of senior citizens [4][5][6]. Research has shown that senior citizens participating in social activities are able to initiate and accrue benefits to their well-being [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leisure activity participation is regarded as a factor that may influence the health of senior citizens [4][5][6]. Research has shown that senior citizens participating in social activities are able to initiate and accrue benefits to their well-being [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Unified Theory of Acceptance and Use of Technology (UTAUT) was applied to explore the relationship among subjective well-being, leisure participation behavior, and the antecedent variables concerning leisure participation behavior (i.e., performance expectancy, effort expectancy, social influence, and facilitating conditions). Prior research has shown that leisure participation behavior is positively associated with individual well-being [4][5][6]. In the literature, no study has employed leisure participation behavior as a mediating construct between subjective well-being and the constructs, such as performance expectancy and social influence, particularly for senior citizens.…”
Section: Introductionmentioning
confidence: 99%
“…There is a consensus about the conceptualization of leisure involvement as a multidimensional construct (Kyle, G., & Chick, 2002). Moving from this point, this consensus involves topics like appeal, importance, self-expression, social relationships, and identification (Kyle, G., & Chick, 2002;Yoon et al, 2020;Xie, et al, 2020).…”
Section: Leisure Involvementmentioning
confidence: 99%
“…Social and productive leisure participation in religious activities, social gatherings, and volunteering have been significantly related to the quality of life in older adults. Moreover, frequent participation in travel and cultural activities outside the home is positively related to life satisfaction [ 20 ]. Physical activity has been significantly related to life satisfaction and happiness in young, middle-aged, and older adults [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%